Do bipolar disorder soft signs impact outcomes following Transcranial Magnetic Stimulation (TMS) therapy for depression? - Bennett, Emily; Almeida, Jorge R.C.; Carpenter, Linda L. (Journal of affective disorders, 2019)
•Bipolar disorder “soft signs” was defined by family history and MDQ response.•Among depressed patients getting TMS, soft signs of bipolar disorder does not diminish response rate.•A switch to mania was not seen in response to TMS in MDD patients with bipolar risk. Transcranial Magnetic Stimulation (TMS) is not currently FDA approved for depressed patients with bipolar disorder (BD), but many unipolar depressed patients presenting for TMS have soft signs of bipolarity. It is not known whether or not these soft signs portend differential outcomes. To investigate the relationship between BD soft signs and TMS treatment outcomes in a naturalistic treatment setting. We conducted a retrospective chart review of MDD patients (n = 105) treated with TMS. BD diathesis was defined by responses to a modified version of the Mood Disorder Questionnaire and family history. TMS response rates for the group with BD diathesis and the group without were equivalent using two self-report depression severity scales. Remission rate was significantly lower for the bipolar soft signs group (13.5% versus 30.2%; p = 0.04) on one scale. This result does not hold when corrected for multiple comparisons. We did not observe switch to mania. These data are limited to patients diagnosed with unipolar depression with “soft” bipolar features defined by subthreshold symptoms. The results cannot be extrapolated to patients with a full bipolar diagnosis. Bipolar diathesis in MDD is not a safety concern but may lead to somewhat lower remission rates when considering TMS treatment.